Intelligent Control of Wind/ Photovoltaic Microgrid Information Fusion - Jianhong Zhu; Wen-xia Pan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
A full-function Micro-grid must have an advanced energy storage device. Intelligent control with multi-information fusion was proposed in this paper. Control targets were acquired by mixed application of various strategies, such as Micro-grid peak load shifting be used to reduce State Utility Grid (SUG) supply pressure, SUG connection be controlled flexibly to maintain Micro-grid load working reliably, Micro-grid power production and load supply demands of SUG and Micro-grid be predicted to plan battery energy storage in advance, actual monitoring date be used to control overcharge and over-discharge, State of Charge (SOC) be managed to realize battery efficient storage  and full life cycle as far as possible. All designs were integrated with forecasting and monitoring data from different locations, such as Micro-grid supply side and demand side, the SOC of storage system, the active and reactive power from SUG side, so as to control the battery charge and discharge behavior and SUG connection operation dynamically. Micro-grid could not only operate stand-alone by self-supply in most cases, in the case of power production surplus or equipment malfunction, the Micro-grid could also delivery energy to SUG or take power from the SUG flexibly. The scheme used fully of new energy, could ensure region power supply reliably and be used widely in application.